2013
DOI: 10.4236/ojap.2013.21004
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Heavy Metals and Microbial Analysis of Soil Samples Collected from the Area around Zliten Cement Factory

Abstract: Soil samples were collected from and around Zliten cement factory, Zliten town, Libya. Soil metals and microbial contents were determined. The results obtained for the examined physiochemical characteristics of soil in the area studied prove that cement dust from the Zliten cement factory in Libya has had a significant impact on the soil. The affected soil properties are pH and total calcium content. These characteristics were found to be higher than those in similar soils from the same area (unpolluted). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Environmental pollution with cement dust by alkaline property affects all ingredients of the ecosystem [8]. Cement dust pollution generally causes alkalization of the ecosystem by changing electrical conductivity, pH, and chemical composition of the soil [1,9]. Increasing soil pH values affects soil biological activities and enzyme activities that are highly related to soil moisture, temperature and pH [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollution with cement dust by alkaline property affects all ingredients of the ecosystem [8]. Cement dust pollution generally causes alkalization of the ecosystem by changing electrical conductivity, pH, and chemical composition of the soil [1,9]. Increasing soil pH values affects soil biological activities and enzyme activities that are highly related to soil moisture, temperature and pH [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Four fungal genera namely Aspergillus, Rhizopus, Penicillium, and Fusarium were isolated in the present study. Such genera were previously reported in different Libyan soils polluted by like these metals such as dust from cement factory [20] and iron and still factory [21]. The increased microbial population at polluted sites by this kind of water may be attributed to different metals which may feed some of these microorganisms [4].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study [68] revealed that Abu-Kammash (Libya) is contaminated with several toxic elements and petrochemical compounds, and that the soil should be not be used for agriculture until it is remediated to ensure human health. In Zliten, an area around a cement factory, the soil physicochemical characteristics (pH, water content, and organic matter) indicate a strong influence of cement dust that has settled on the soil from the factory [69].…”
Section: Pollutionmentioning
confidence: 99%